SECULARIZATION AND ITS IMPLICATION FOR THE SCIENCES - Nur Hadi Ihsan; Jamal Jamal; Rahmat Ardi Nur Rifa Da'i; Abdul Rohman; Khairul Atqiya (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Secularism assumes that scientific progress can only be built by separating it from religion, because the basis of truth for the two is different. The truth of religion is spiritual-transcendental, while the truth of science is rational-empirical. The impact of the development of science based on secularism will be the focus of the study in this paper. This research is a literature review with a qualitative approach. The data were obtained using documentary techniques and the collected data were analyzed by descriptive-critical-analytical methods. This study concludes that secularization is a natural emptying of religious values ​​and teachings. The worst impact of this ideology is that the development of science in the future will only occur and is limited in the empirical dimension. This research proves that in reality, science is beyond the realm of pure empirical and experimental. Existence has unobservable and non-empirical elements that are real and true. This perspective will increase the significance of scientific discoveries that are not limited to the empirical world alone and at the same time make scientific research will have a more meaningful impact on human life as a whole.